Implementasi Kurikulum Merdeka Pada Pelajaran Fiqih Kelas VII Di MTs Darut Taqwa 02 Pasuruan - Rifqotus Sa’idah; Achmat Mubarok (4, 2025)
This study, which examines the implementation of the Independent Curriculum in Fiqh for seventh-grade students at MTs Darut Taqwa 02 Sengonagung Purwosari, is motivated by the continued development of education in Indonesia, one of which is through the implementation of the Independent Curriculum. This curriculum aims to provide flexibility and relevance in learning. This study focuses on how the Independent Curriculum is implemented in Fiqh for seventh-grade students at MTs Darut Taqwa 02 Sengonagung Purwosari, Purwosari, Purwosari. The approach used qualitative methods, with data sources obtained from observation, interviews, and documentation. The main focus of the research is to understand social phenomena in depth and contextually. The purpose of this qualitative study is to gain a rich and descriptive understanding of how the Independent Curriculum is implemented in Fiqh. This study yields the following results: 1) The implementation of the Independent Curriculum in Fiqh is carried out through appropriate teaching tools, active methods, and learning media. The material focuses on understanding, practicing, and applying Islamic jurisprudence values. School support in the form of flexible strategies, teacher training, and project evaluations makes Islamic jurisprudence learning more contextual, active, and relevant. 2) Islamic jurisprudence teachers at MTs Darut Taqwa 02 Sengonagung Purwosari Pasuruan improve the learning of the Independent Curriculum by understanding curriculum principles, developing relevant materials, and encouraging students to think critically and independently. Teachers also participate in training, collaborate, use diverse learning resources, and engage in reflection. These efforts make Islamic jurisprudence learning more effective, contextual, and tailored to students' needs. Abstrak Penelitian Implementasi Kurikulum Merdeka Pada Mata Pelajaran Fiqih Kelas VII di MTs Darut Taqwa 02 Sengonagung Purwosari dilatar belakangi oleh terjadinya pendidikan di Indonesia yang terus berkembang, salah satunya melalui implementasi Kurikulum Merdeka. Kurikulum ini bertujuan memberikan fleksibilitas dan relevansi dalam pembelajaran. Penelitian ini berfokus pada bagaimana Kurikulum Merdeka diterapkan pada mata pelajaran Fiqih kelas VII di MTs Darut Taqwa 02 Sengonagung Purwosari Psuruan. Pendekatan dalam penelitian ini menggunakan metode kualitatif, sumber data diperoleh dari: observasi, wawancarara , dan dokumentasi. fokus utama penelitian adalah untuk memahami fenomena sosial secara mendalam dan kontekstual. Tujuan dari penelitian kualitatif ini untuk memperoleh pemahaman yang kaya dan deskriptif tentang bagaimana Kurikulum Merdeka diimplementasikan pada mata pelajaran Fiqih. Penelitian ini menghasilkan : 1) Implementasi Kurikulum Merdeka pada mata pelajaran Fiqih dilakukan melalui perangkat ajar yang sesuai, metode aktif, dan media pembelajaran. Materi difokuskan pada pemahaman dan praktik, serta penerapan nilai-nilai fiqih. Dukungan sekolah berupa strategi fleksibel, pelatihan guru, dan evaluasi proyek membuat pembelajaran Fiqih lebih kontekstual, aktif, dan relevan. 2) Guru Fiqih di MTs Darut Taqwa 02 Sengonagung Purwosari Pasuruan meningkatkan pembelajaran Kurikulum Merdeka dengan memahami prinsip kurikulum, menyusun materi yang relevan, serta mendorong siswa berpikir kritis dan mandiri. Guru juga mengikuti pelatihan, berkolaborasi, menggunakan sumber belajar beragam, dan melakukan refleksi. Upaya ini menjadikan pembelajaran Fiqih lebih efektif, kontekstual, dan sesuai kebutuhan siswa.